2017
DOI: 10.1103/physrevlett.118.208101
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Metric Correlations in Two-Dimensional Neuronal Cultures Described through a Random Field Ising Model

Abstract: We introduce a novel random field Ising model, grounded on experimental observations, to assess the importance of metric correlations in cortical circuits in vitro. Metric correlations arise from both the finite axonal length and the heterogeneity in the spatial arrangement of neurons. The experiments consider the response of neuronal cultures to an external electric stimulation for a gradually weaker connectivity strength between neurons, and in cultures with different spatial configurations. The model can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…S3). The similarity in the dynamics was due to the small size of the cultures in comparison to the axonal length and that favored a broad network interconnectivity, both between neurons and aggregates [19]. Only in the case of extreme aggregation coherent collective dynamics was replaced by fragmented, local activity [26].…”
Section: Simulation Of Spatial Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…S3). The similarity in the dynamics was due to the small size of the cultures in comparison to the axonal length and that favored a broad network interconnectivity, both between neurons and aggregates [19]. Only in the case of extreme aggregation coherent collective dynamics was replaced by fragmented, local activity [26].…”
Section: Simulation Of Spatial Networkmentioning
confidence: 99%
“…The increase of structural connectivity upon aggregation highlights that metric correlations may prove essential to understand the behavior of neuronal networks. Hernández-Navarro et al [19] recently showed that the role of spatial embedding in the structure and dynamics of networks can be quantified in terms of the degree of aggregation λ and the relative axonal length δ = a/L, where a is the average axonal length and L the diameter of the culture.…”
Section: Aggregation and Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Recent studies showed that spatial embedding in these systems naturally feature metric correlations that shape in great measure the architectural and dynamic traits of the neuronal network. 14,[16][17][18] To the best of our knowledge, there exist no computational studies for damage that take into account the spatial embedding of biologically-realistic neuronal microcircuits. Thus, in the present study, we aim at lling this gap by introducing a detailed numerical exploration of the di erences between targeted attack and failure in spatially-embedded networks.…”
Section: Articlementioning
confidence: 99%
“…Note that connections cross the window also from neurons outside of the field of view, such that single connections cannot be distinguished visually in the sketch. (b) 1.4 × 1.4mm 2 subset of spatially-clustered (SC) topology generated by axonal-growth rules[5,88].…”
mentioning
confidence: 99%